Strategy for the Sociocultural Competence in the Foreign Languages Major - Geovel Gómez Remedio; Vilma Violeta Borrero Ochoa; Sonia Vargas Suárez (Revista MENDIVE, 2023)
The sociocultural competence is a feasible topic due to its importance in the development of the communicative competence. The research was characterized for being a pedagogical professional approach. The objective of this article was to determine the causes of the insufficient development of the sociocultural competence in Foreign Language teacher trainees limiting the pedagogical performance, so as the establishment of the solution throughout an interventive strategy. In this study, the main categories taken into account are the sociocultural competence and the didactic-sociocultural competence. The research methods used were the following: participant observation, interviews, surveys, pedagogical test and study of the activity products. These methods correspond to the participatory action research methodology of the qualitative paradigm. As a fundamental result of the investigation, the following causes were determined that allowed the origins of the difficulties of the teacher trainees related to the topic that is researched are shown and the corresponding actions for the interventive strategy, which main theoretical base is the didactic-sociocultural competence. In the same way, it is concluded the feasible truth of the previously established theoretical limitation.